Can Different Fermentation Boxes Improve the Nutritional Composition and the Antioxidant Activity of Fermented and Dried Floodplain Cocoa Beans in the Brazilian Amazon? - Sabrina Oriana de Souza Begot da Rocha; Maria do Perpétuo Socorro Progene Vilhena; Jesus Nazareno Silva de Souza; César R. Balcázar-Zumaeta; Efraín M. Castro-Alayo; Alexa J. Pajuelo-Muñoz; Braian Saimon Frota da Silva; Maria José de Souza Trindade; Gilson C. A. Chagas-Junior; Nelson Rosa Ferreira (Foods)
This study evaluated the impact of different fermentation boxes on the nutritional and antioxidant composition of dried lowland cocoa beans (Theobroma cacao L.), a characteristic product of some producers in the Amazon region. The analysis included ash content, moisture content, pH, titratable acidity, proteins, lipids, flavonoids, antioxidant activities (DPPH, ABTS, and FRAP), and mineral composition. Four types of fermentation boxes were assessed: a projected hexagonal box (PHB), square box (SB), basket (HP), and local square box (LSB). Statistical analyses included ANOVA, Tukey’s test, and Fisher’s LSD test to compare mean differences, while Principal Component Analysis (PCA) identified key contributors, including potassium and magnesium. Spearman correlation analysis revealed significant relationships between soil and almond nutrient profiles. The HP bed exhibited superior phenolic concentration, antioxidant activity, centesimal composition, and potassium and magnesium content. Despite its shorter fermentation period, the LSB bed met quality standards, while the PHB and SB showed intermediate results. Mineral analysis confirmed no toxicological risks, suggesting the beans are safe and enriched with floodplain minerals. These findings emphasize the importance of fermentation methods in determining cocoa bean quality and provide a framework for optimizing processes to enhance their nutritional and functional properties.